ENHANCING BREAST MILK PRODUCTION THROUGH THE EFFECTIVENESS OF MUSIC THERAPY: A STUDY IN TERMS OF FREQUENCY, TYPE, AND DURATION OF MUSIC - Putri, Harlinda Widia; Putri, Sartika Dwi Yolanda; Mumtazah, Siti Ainawati; Sari, Puja Maya; Sihotang, Pasuria; Widyasari, Esti; Sulistyaningsih, Sulistyaningsih (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Music therapy is one of the non-pharmacological treatment methods used to increase milk production. Music stimulates the release of the hormone oxytocin and endorphins, so that it can increase milk production. Considering the frequency, type and duration of music is indeed pivotal in music theraphy instead of the music intervention.Purpose: to enhance breast milk production through the effectiveness of music therapy in terms of frequency, type,and duration of music.Method: The PICO (Population, Intervention, Comparison, and Outcome) framework is used as the basic to formulate the research questions. Besides, the EBSCO, Wiley, PubMed, and Google Scholar databases are also used as the literature study. PRISMA Flowchart and critical appraisal are implemented in selecting the article.Results: of the synthesis contained 5 articles that met the inclusion criteria. This review found that music therapy may be a method that can be used to increase relaxation and increase milk production.Conclusion: The effectiveness of music therapy is maximum if mother plays their favourite music. The best music type for this therapy is a passive music that provided relax sensation through the lyrics and harmony such as the bounding between mother and her child.